Exploring the extrachromosomal plasmid rDNA of Naegleria fowleri AY27 genotype II: A human brain-eating amoeba via high-throughput sequencing - Muhammad Aurongzeb; Hafiz Muhammad Talha Malik; Muhammad Jahanzaib; Syed Shah Hassan; Yasmeen Rashid; Tariq Aziz; Metab Alharbi (BMC, 2024)
Abstract Naegleria fowleri, also known as brain-earing amoeba, causes severe and rapidly fatal CNS infection in humans called primary amebic meningoencephalitis (PAM). The DNA from the N. fowleri clinical isolate was sequenced for circular extrachromosomal ribosomal DNA (CERE - rDNA). The CERE contains 18 S, 5.8 S, and 28 S ribosomal subunits separated by internal transcribed spacers, 5 open reading frames (ORFs), and mostly repeat elements comprising 7268 bp out of 15,786 bp (46%). A wide variety of variations and recombination events were observed. Finally, the ORFs that comprised only 4 hypothetical proteins were modeled and screened against Zinc drug-like compounds. Two compounds [ZINC77564275 (ethyl 2-(((4-isopropyl-4 H-1,2,4-triazol-3-yl) methyl) (methyl)amino) oxazole-4-carboxylate) and ZINC15022129 (5-(2-methoxyphenoxy)-[2,2'-bipyrimidine]-4,6(1 H,5 H)-dione)] were finalized as potential druggable compounds based on ADME toxicity analysis. We propose that the compounds showing the least toxicity would be potential drug candidates after laboratory experimental validation is performed.